2013
DOI: 10.4172/2161-1149.s5-005
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake Improves Adherence of Pregabalin and Tramadol/Acetaminophen to RA and OA Patients

Abstract: Clinical managements of chronic pain in rheumatoid arthritis (RA) and osteoarthritis (OA) require deep understanding of patients. Since medication is mostly set under the guidelines of RA and OA to control of pain, but personal characteristics is not so much paid attention in terms of preferences. In the present study, alcohol preference was analyzed in the patients prescribed pregabalin and tramadol/acetaminophen in our hospital. All consecutive patients were requested to write up the medical questionnaire sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Very few studies have shown correlations between lifestyle factors and adherence in RA patients. Alcohol drinkers vs. non-alcohol drinkers showed good adherence with pregabalin (81% vs. 61%) and tramadol/acetaminophen (88% vs. 65%) in RA patients [12].…”
Section: Introductionmentioning
confidence: 95%
“…Very few studies have shown correlations between lifestyle factors and adherence in RA patients. Alcohol drinkers vs. non-alcohol drinkers showed good adherence with pregabalin (81% vs. 61%) and tramadol/acetaminophen (88% vs. 65%) in RA patients [12].…”
Section: Introductionmentioning
confidence: 95%